Fios, tramas, cores, repassos e inventabilidade: a formação de tecelãs em Resende Costa/MG - Castro, Amanda Motta (Universidade do Vale do Rio dos Sinos, 2015)
The dissertation analyses how the pedagogical process of teaching and learning manual weaving occurs among women in the city of Resende Costa, Minas Gerais, Brazil. The methodology of investigation was based on the participant research done through semi-structured interviews and participant observation. There were two immersions in that location in the years of 2011 and 2012, both in the month of July. The data analisys was based on Feminist hermeneutics and Popular Education. Among the results, it was observed that the process of artisanal production comprehends a series of techniques and knowledge automatized and invisibilized for basically being a female production, the complexity perceived by the one of who researches seems to disappear in the lives of the artisans, giving place to the invisible. This study concluded also, that one of the richest processes in the formation of the weavers takes place through the necessity and desire of sharing: the passing forward. A concept which we established as being a singular method in the singular action of keeping the tradion of weaving in a living flood of passing forward what the most experient artisans have and pass forward to other women who they chose to be the new owners of the techniques of weaving.
Keywords: Educação popular; Estudos feministas; Tecelagem manual; Formação; Popular education; Feminist studies; Manual weaving; Formation; ACCNPQ::Ciências Humanas::Educação